Proceedings of the 5th ACM Conference on Bioinformatics, Computational Biology, and Health Informatics 2014
DOI: 10.1145/2649387.2649413
|View full text |Cite
|
Sign up to set email alerts
|

Approximation algorithms for sorting by signed short reversals

Abstract: During evolution, global mutations may modify the gene order in a genome. Such mutations are commonly referred to as rearrangement events. One of the most frequent rearrangement events observed in genomes are reversals, which are responsible for reversing the order and orientation of a sequence of genes. The problem of sorting by reversals, that is, the problem of computing the most parsimonious reversal scenario to transform one genome into another, is a well-studied problem that finds application in comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this section, we present basic definitions that are used throughout this paper, generally following [ 28 ]. Let n be a positive integer.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present basic definitions that are used throughout this paper, generally following [ 28 ]. Let n be a positive integer.…”
Section: Preliminariesmentioning
confidence: 99%
“…In preliminary work, Galvão and Dias [ 28 ] investigated the problem of sorting a signed permutation by reversals of length at most 3 and presented three approximation algorithms, the best one having an approximation factor of 9. In this paper, we not only present an approximation algorithm with a better approximation factor, but also consider other bounded variants.…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary work, we [Galvão and Dias 2014a] investigated the problem of sorting a signed permutation by reversals of length at most 3 and presented three approximation algorithms, the best one having an approximation factor of 9. In Chapter 5, we not only present an approximation algorithm with a better approximation factor, but also consider other variants of the problem.…”
Section: Contributions and Organizationmentioning
confidence: 99%
“…Dias and Meidanis [7] presented a 2-approximation algorithm for Sbpt, here called 2-PT, which always removes one breakpoint with one prefix transposition. They also demonstrated that there is at most one prefix transposition that removes two breakpoints at once, which leads to a greedy 2-approximation algorithm for the problem, called 2-PTg [10]: first it tries to remove two breakpoints and if this is not possible, it removes only one, as 2-PT does. Therefore, both guarantee that d Θp (Θ) ⊕ b Θp (Θ)− 1, since the last transposition always removes two breakpoints [7], and both are 2-approximation algorithms.…”
Section: Algorithms For Sbptstmentioning
confidence: 99%